2005
DOI: 10.1007/s11910-005-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in multiple sclerosis: A rational approach to evaluation and treatment

Abstract: With the publication of the Multiple Sclerosis Council Guideline on the management of multiple sclerosis (MS) fatigue, there has been increased appreciation for the role fatigue can play in MS. Secondary fatigue is fatigue caused by other etiologies than those directly related to MS. Once these causes are ruled out, fatigue is related to MS. Secondary MS-related fatigue comes as result of the symptoms of MS that drain energy. Once secondary MS causes are ruled out, then the patient is deemed as having primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Amantadine has been found to be potentially useful in the management of fatigue associated to multiple sclerosis [56][57][58], but -to our knowledge -it has not been formally tested as treatment for this symptom in PD [59,60]. Although the present study was not aimed at exploring therapeutic aspects, this finding might be considered for future studies.…”
Section: Discussionmentioning
confidence: 91%
“…Amantadine has been found to be potentially useful in the management of fatigue associated to multiple sclerosis [56][57][58], but -to our knowledge -it has not been formally tested as treatment for this symptom in PD [59,60]. Although the present study was not aimed at exploring therapeutic aspects, this finding might be considered for future studies.…”
Section: Discussionmentioning
confidence: 91%
“…Following application of the exclusion criteria, we enrolled 34 clinically-stable patients with a MMSE ranging from 16 [26] . Functional status was evaluated by means of the Barthel Index [27] and Rivermead Mobility Index [28] which are commonly used in the management of patients with neurological disorders.…”
Section: Methodsmentioning
confidence: 99%
“…The symptomatic treatment of CI in MS using drugs such as Amantidine and Modafinil has been investigated in several studies, most of which focus on fatigue [16] . The positive effect of Donepezil on memory function in MS patients reported by Krupp et al [17] has yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Although the FSS is fast and easy to administer, it is not highly sensitive for detecting change, due to the limited range of possible scores. A small change is therefore significant [6]. The Modified Fatigue Impact Scale (MFIS) is a 21 item questionnaire, allowing the calculation of scores for physical, cognitive, and psychosocial subscales, as well as an overall score (0 to 84) [2].…”
Section: Fatigue In Msmentioning
confidence: 99%